One‐year outcome after transcatheter aortic valve replacement for aortic regurgitation: A single‐center study. Issue 4 (18th January 2022) - Liu, Lulu; Yao, Xiaoling; Peng, Ying; Huang, Weina; Jun, Shi; Qian, Hong; Chen, Yilong; Guo, Yingqiang
Abstract: Background: Presently, there are limited reports in the literature on the postoperative (midterm) clinical outcome for pure aortic regurgitation (AR) following transcatheter aortic valve replacement (TAVR). Methods: Between March 2014 and June 2019, a total of 134 high‐risk patients with pure, symptomatic severe AR patients were enrolled in the current study. The outcome was assessed according to the Valve Academic Research Consortium‐2 criteria. Procedural results, clinical outcomes, and the patients' hemodynamics for a period of 1 year were analyzed. Results: The patient mean was 73.1 ± 6.4 years and 25.4% were female. The average Society of Thoracic Surgeons score was 9.8 ± 5.3%. Procedural success was 97.1% (130/134), and the device success rate was 96.3% (129/134). Five cases were converted to open surgery, while two patients underwent valvular reinterventions (surgical aortic valve replacement for thrombosis and increasing paravalvular regurgitation). The mean aortic valve gradient was 10.2 ± 4.1 mmHg, while the moderate and severe AR was 1.6% at 1 year. Paravalvular regurgitation was none/trivial in 79.8% and mild in 18.5%. The 1‐year all‐cause mortality rate was 7.4%. At 1 year, the stroke incidence rate was 2.2%,  and a pacemaker was implanted in 8.9% of the enrolled patients. Conclusions: In high‐risk patients undergoing transapical TAVR for AR, the use of the J‐Valve is safe, and effective TAVR should be considered as a reasonable option for high‐risk patients with pure AR.